Cerita dari Posyandu: Pengalaman Orang Tua dalam Mendeteksi Tumbuh Kembang Anak - Restya, Dhifa Noor; Khoerunnisa, Abelia; Karomatunnisa, Nita; Yuniar, Riska; Muqodas, Idat; Nikawanti, Gia; Ardiyanti, Dhea (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
This community service activity examines parental involvement in early detection of child development through Posyandu services in Margamukti Village, Pangalengan District. Using a qualitative approach involving participatory observation and in-depth interviews, data was collected from two informants who regularly visit Posyandu. The results showed that Posyandu plays an important role in supporting early detection of child development, especially in monitoring weight, height and nutritional status. However, there are gaps in parents' understanding of certain developmental indicators, such as speech milestones and emotional regulation. Informants emphasized the importance of Posyandu services but also highlighted the need for more in-depth education on child development. Challenges include low health literacy among some parents and limited understanding of early detection practices. Recommendations include personalized counseling through a door-to-door approach and increased education programs led by Posyandu cadres to bridge this gap. This activity underscores the importance of parental engagement and targeted education efforts to ensure optimal child development outcomes.